2020
DOI: 10.3390/agronomy10020246
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water-Salt Dynamics and Maize Growth as Affected by Cutting Length of Topsoil Incorporation Straw under Brackish Water Irrigation

Abstract: Brackish water has been utilized extensively in agriculture around the world to cope with the global water deficit, but soil salt accumulation caused by brackish water irrigation cannot be ignored. Straw incorporation has been confirmed an effective sustainable means to inhibit soil salt accumulation. An experiment was conducted in growth tanks over two consecutive growing seasons to investigate the effects of wheat straw incorporation on soil moisture and salinity under brackish water irrigation (5g NaCl L−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Shorter straw favorably and significantly decreased soil bulk density, which provided more oxygen to enhance the activity of microorganisms and enzymes. The shorter the straw was cut, the easier it was to decompose [ 15 ]. This study has concluded that the decomposition rate and organic carbon decomposition rate decreased with the increase of tomato remnant cutting length and both were negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter straw favorably and significantly decreased soil bulk density, which provided more oxygen to enhance the activity of microorganisms and enzymes. The shorter the straw was cut, the easier it was to decompose [ 15 ]. This study has concluded that the decomposition rate and organic carbon decomposition rate decreased with the increase of tomato remnant cutting length and both were negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sequestration and stocks is a double-edged sword to environmental climate change. However, in agricultural production systems, fresh straws contain more dissolved organic carbon and cause a rapid decomposition and mineralization in soil [ 15 ]. The easier straws are decomposed and mineralized, the more soil dissolved organic matter are released, which rapidly transform plant remnants into microbe-decomposed products and provide sufficient plant nutrients than those in dried plant remnants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wheat straw (Hebei, China) collected as the substrate contained 39.3% cellulose (Van Soest method), 32.2% hemicellulose (DNS reagent method) and 11.3% lignin (Van Soest method). The rice straw which had been air-dried was cut into 3-5 cm length and mechanically crushed into powder (passing through 20 meshes sieve), dried in an oven at 60°C to a constant weight [17].…”
Section: Pretreatment Of Wheat Strawsmentioning
confidence: 99%
“…The use of organic compounds of animal origin as organic fertilizer is a useful and economic practice widely used by farmers in the Brazilian semi-arid region. This practice mitigates the effect of soil salinity, through the production of humic acids and organic acids, promoting an increase in carbonate solubilization (9,10,11) , providing a delay in the effect of adding salts to the soil by irrigation and leaching of these salts during the rainy season in semi-arid regions (12) . According to Silva et al (13) , organic fertilizer incorporated into the soil improves the physical structure, reducing the soil mass, which favors soil porosity and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%